Taxonomic notes on Leandra cordifolia (Melastomataceae) - Caddah, Mayara Krasinski; Meirelles, Julia (Phytotaxa, 2018)
A recent survey on Melastomataceae from the state of Santa Catarina, southern Brazil (Feldhaus et al. in prep.) revealed the problematic circumscription among Leandra cordifolia (Naudin) Cogniaux (1886: 98) and related taxa, here formally treated in order to untangle the case.